If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 6x) + -3 = 63 (3 * 2 + 6x * 2) + -3 = 63 (6 + 12x) + -3 = 63 Reorder the terms: 6 + -3 + 12x = 63 Combine like terms: 6 + -3 = 3 3 + 12x = 63 Solving 3 + 12x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 12x = 63 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = 63 + -3 12x = 63 + -3 Combine like terms: 63 + -3 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| x^4-15x^3+69x^2-63x-148=0 | | 7(3x+6)=294 | | -1/(x-1)^2 | | 4d-13=31 | | F=6(7+2) | | 21x=-7 | | 5v-7=23 | | x^2-10x=-19 | | 100=-4s | | -78=6h | | X+2/5=x/6 | | 7/x-3/w | | z-0.9=-4.8 | | X+2/x+1=0 | | 6(2m-10)=5(14+2m) | | 8x+4(4x-3)=4(x+4)-4 | | -1+s=5 | | 9+(2/u-1)=(-4/u-2) | | 3x-(-4-2x)+7x=10x+2(16-3x) | | 17-x=1/315+6 | | x+2y=y | | p+(-8)=-12 | | 3c+11=50 | | -6=g+4 | | (-30)(30000)= | | 6y+y=-70 | | 6(2-2x)=0 | | 5(7-4x)=-125 | | abs(8x+2)=abs(x+2) | | -10t=200 | | 12X+4/2X+7=4 | | -7(2x+3)=-147 |